2021
DOI: 10.1177/01461672211015062
|View full text |Cite
|
Sign up to set email alerts
|

Do You Feel Better When You Behave More Extraverted Than You Are? The Relationship Between Cumulative Counterdispositional Extraversion and Positive Feelings

Abstract: The idea that increased levels of extraversion are beneficial to well-being is widespread. Drawing on the idea that behaving discordant to one’s trait level is demanding and effortful to maintain, and that repeated taxations of one’s self-regulatory resources are unpleasant, we examined the relationship between cumulative counterdispositional extraversion and positive feelings. In two experience-sampling (ESM) studies, participants repeatedly rated their level of state extraversion and positive feelings. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Given the potential context control has over traitrelated control in improving coping, it is this type that is measured. Important personality ingredients, related to coping, include those measured by the Big Five [42], including extraversion [43] and conscientiousness, levels of emotional stability and openness [44]-in education contexts, openness is important if learning is to expand; and optimistic thinking strategies have been associated with improved wellbeing, performance and health [45][46][47]. Those scoring high on optimism construe stress demands in a way that makes success more likely.…”
Section: Coping With Stressmentioning
confidence: 99%
“…Given the potential context control has over traitrelated control in improving coping, it is this type that is measured. Important personality ingredients, related to coping, include those measured by the Big Five [42], including extraversion [43] and conscientiousness, levels of emotional stability and openness [44]-in education contexts, openness is important if learning is to expand; and optimistic thinking strategies have been associated with improved wellbeing, performance and health [45][46][47]. Those scoring high on optimism construe stress demands in a way that makes success more likely.…”
Section: Coping With Stressmentioning
confidence: 99%
“…Extraverted individuals experience more positive moods (Watson & Clark, 1997), engender positive affect in others (Eaton & Funder, 2003), and have lower levels of emotion suppression (Vater & Schröder-Abé, 2015). Indeed, the link between behaving in an extraverted manner and experiencing positive affect has consistently emerged from personality science (Fleeson et al, 2002;Kuijpers et al, 2021;McNiel & Fleeson, 2006;McNiel et al, 2010;Smillie et al, 2012Smillie et al, , 2015Watson & Clark, 1997;Zelenski et al, 2013). Moreover, in research probing the mediators of the relationship between enacting extraversion and positive affect, evidence suggests that positive social experiences (e.g., perceived impact on social world, perceived contribution to a discussion) are likely mechanisms (Smillie, 2013).…”
Section: People Remaining In the Leadership Networkmentioning
confidence: 99%
“…It is therefore essential to look beyond isolated effects and include a cumulative effects assessment. One study that explored cumulative effects of counterhabitual behavior revealed that cumulative negative deviations from one's baseline (i.e., acting less extraverted than usual) related negatively to positive feelings, while cumulative positive deviations (i.e., acting more extraverted than usual) were positively related to positive feelings (Kuijpers et al, 2021). It remains an open question, however, whether similar effects hold for conscientiousness.…”
Section: Concurrent Lagged and Cumulative Effects Of Conscientiousnes...mentioning
confidence: 99%
“…In the current study, sample size in terms of the number of repeated measurements was similar with N = 1,699 repeated measures from 157 participants. For cumulative effects, Kuijpers et al (2021) collected 347 cumulative (weekly) observations from 83 individuals (in their Study 1), showing that when people repeatedly behave more extraverted than they typically do, they experience more positive feelings. Our sample size was again similar with 344 cumulative (daily) observations from 117 individuals.…”
Section: Sample Size Considerationsmentioning
confidence: 99%
See 1 more Smart Citation